PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN DAN DIMODERASI OLEH SUKU BUNGA - Raisa, Angela; Jonnardi, Jonnardi (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain evidence regarding the effect of profitability, leverage, and liquidity on firm value with interest rates as a moderating variable for consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The number of samples in this study amounted to 50 consumer non-cyclicals companies selected by simple random sampling method. This study was analyzed using multiple linear regression analysis which was processed with Eviews 12 Full Version software. The results of this study indicate that profitability and leverage have a positive and significant effect on firm value. Liquidity have a negative insignificant effect on firm value. Interest rates are able to moderate the effect of profitability and leverage on firm value in a significantly negative way. Interest rates are not able to moderate the effect of liquidity on firm value.